Rasch Test for Digital Learning Material Development Based on MOOCS - Kusen Kusen (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to examine the needs of students for digital teaching materials based on MOOCs. The research was carried out in February 2022. The research sample was 75 postgraduate students from 4 study programs, namely Guidance and Counseling, Islamic Family Law, Islamic Education Management, and Islamic Religious Education. The research instrument used was a questionnaire on the needs of IAIN Curup postgraduate students for digital teaching materials based on MOOCs. The test and data analysis technique used is the Rasch model analysis with the help of the Winstep application. The result of this research is that MOOCs-based digital teaching materials are very much needed by IAIN Curup postgraduate students. This is evidenced by the percentage value ofalpha cronbach 0.96 belongs to the special category which means that students strongly agree with the development.